Tutor profile: Cameron B.
What are the essential steps to writing an argumentative thesis statement?
The thesis statement is the roadmap of your essay. It explains the main point that you are conveying to your audience and it gives them a glimpse of how you plan to support your argument. The first step to creating this thesis statement is to come up with a topic that is not too general nor too specific. If it is too general, there will be too much information to cover in your supporting paragraphs, which can reduce the effectiveness and conciseness of your argument. If it too specific, you may not be able to find enough supporting information to create a strong argument. Once you have narrowed down your topic, give reasons you support this topic. You will expand upon these reasons in the following paragraphs with evidence and logical facts. Lastly, an important step to creating your argumentative thesis is to include the opposing view that you will be refuting in your essay.
If 7x = 2y - 5 and x = -3, then y =
Step 1: Plug in x. 7x = 2y - 5 (original problem) 7(-3) = 2y - 5 (plug in x) -21 = 2y - 5 (simplify) Step 2: Get y by itself -21 + 5 = 2y - 5 + 5 (add 5 to each side) - 16 = 2y (simplify) -16/2 = 2y/2 (divide 2 on each side) -8 = y Step 3: Check your answer! You can do this by plugging in x and y. 7(-3) = 2(-8) - 5 (plug in x and y) -21 = -16 - 5 (simplify) -21 = -21 correct!
Solve for x. 2x^2 + 6x - 20.
Step 1: Find what numbers would multiply to get -20 and add to get 6 (don't forget the 2 in front of x^2). Since 20 is negative and 6 is positive, we know that one of the unknown numbers must be negative = (2x + ___ )(x - ____ ) Step 2: Plug in the numbers that would multiply to get -20 and add to get 6. In this case, that would be (2x + 10)(x - 2). Step 3: Now that we have simplified the equation, it is easier to find x. Set each equation within the parentheses equal to 0. (2x + 10) = 0 (x - 2) = 0 Step 4: Solve for x x = -5 x = 2 Step 5: Don't forget to check your answers! You can do this by plugging your x back into the question. (2(-5) + 10)(-5 - 2) = (-10 + 10)(-7) = (0)(-7) = 0 correct! (2(2) + 10)(2 - 2) = (4 + 10)(0) = (14)(0) = 0 correct!
needs and Cameron will reply soon.